Anodic electron sheaths in low pressure hollow cathode discharge with large size anode - Bazhenov, V.Yu.; Matsevich, S.V.; Piun, V.M.; Tsiolko, V.V. (Вопросы атомной науки и техники, 2015)
Researches of the features of “electron” sheath formed between the negative glow plasma and the anode of hollow cathode discharge in oxygen and nitrogen at low pressure are performed. Peculiarities of behavior of spatial distributions of current onto the anode, plasma density and electron temperature are determined at different gas pressure and discharge current. Проведены исследования свойств электронного слоя, формирующегося между плазмой отрицательного свечения и анодом разряда с полым катодом в кислороде и азоте низкого давления. Установлены особенности поведения пространственного распределния плотности тока на анод, плотности плазмы и электронной температуры при различных давлениях газов и разрядных токах. Проведено дослідження властивостей електронного шару, що формується між плазмою негативного світіння та анодом розряду з порожнистим катодом у кисні та азоті низького тиску. Встановлено особливості поведінки просторового розподілу густини струму на анод, густини плазми та електронної температури при різних тисках газів та розрядних струмах.